Assessment of Pollen Viability for Wheat - Impe, Daniela; Reitz, Janka; Köpnick, Claudia; Rolletschek, Hardy; Börner, Andreas; Senula, Angelika; Nagel, Manuela (Frontiers in Plant Science, 2020)
Wheat sheds tricellular short-lived pollen at maturity. The identification of viable pollen required for high seed set is important for breeders and conservators. The present study aims to evaluate and improve pollen viability tests and to identify factors influencing viability of pollen. In fresh wheat pollen, sucrose was the most abundant soluble sugar (90%). Raffinose was present in minor amounts. However, the analyses of pollen tube growth on 112 liquid and 45 solid media revealed that solid medium with 594 mM raffinose, 0.81 mM H3BO3, 2.04 mM CaCl2 at pH5.8 showed highest pollen germination. Partly or complete substitution of raffinose by sucrose, maltose or sorbitol reduced in vitro germination of the pollen assuming a higher metabolic efficiency or antioxidant activity of raffinose. In vitro pollen germination varied between 26 lines (P<0.001); between winter (15.3±8.5%) and spring types (30.2±13.3%) and was highest for the spring wheat TRI 2443 (50.1±20.0%). Alexander staining failed to discriminate between viable, fresh pollen and non-viable pollen inactivated by ambient storage for >60 min. Viability of fresh wheat pollen assessed by fluorescein diacetate (FDA) staining and impedance flow (IF) cytometry was 79.2±4.2% and 88.1±2.7%, respectively; and, when non-viable, stored pollen was additionally tested, it correlated at r=0.54 (P<0.05) and r=0.67 (P<0.001) with in vitro germination, respectively. When fresh pollen was used to assess the pollen viability of 19 wheat, 25 rye, 11 barley and 4 maize lines, correlations were absent and in vitro germination was lower for rye (11.7±8.5%), barley (6.8±4.3%) and maize (2.1±1.8%) pollen compared to wheat. Concluding, FDA staining and IF cytometry are used for a range of pollen species, whereas media for in vitro pollen germination require specific adaptations; in wheat, a solid medium with raffinose was chosen. On adapted media, the pollen tube growth can be exactly analyzed whereas results achieved by FDA staining and IF cytometry are higher and may overestimate pollen tube growth. Hence, as the exact viability and fertilization potential of a larger pollen batch remains elusive, a combination of pollen viability tests may provide reasonable indications of the ability of pollen to germinate and grow.